Development of Intelligent High Rate LED Driver Module - Hyeog Moon, Seung; ., . (International Journal of Engineering and Technology, 2018)
Background/Objectives: Concerns over need for eco-friendly LED lighting to replace existing lighting source are outweighed by energy efficiency ratio and interest in environmental protection recently. Measures to solve the generated heat which increases proportionally with high powered light are needed. Research and development to solve problem such as LED chip and package module is being vigorously pushed forward because technology of protection against heat has such a big influence on efficiency of LED lighting as well as lifespan.Methods/Statistical analysis: It is checked status of domestic and foreign technology development and driver module for high efficiency intelligent LED with self-awareness function is developed. Technology of intelligent LED lighting is to be extend. Standardization of control method for illumination sensitivity is performed and sensor controller of intelligent LED lighting is to secure in this study.Â Findings: High efficiency intelligent LED driver module with self-awareness is developed and is able to accumulate its technology. Acquisition of LED dimming technology also makes it possible not only to control illumination sensitivity but also to acquire technology of sensor and its control related to LED street lights as well as security lights.Improvements/Applications: Driver module for high efficiency intelligent LED with self-awareness function is developed. It is expected to find new market and cost saving effect of electric charges by effective management and effect of extension of life span will be expected. The expansion of application industry is expected according to secure new technology.Â Â